Characterization of Surface Receptor Expression and Cytotoxicity of Human NK Cells and NK Cell Subsets in Overweight and Obese Humans - Naujoks, Wiebke; Quandt, Dagmar; Hauffe, Anja; Kielstein, Heike; Bähr, Ina; Spielmann, Julia (Frontiers in Immunology, 2020)
Obesity is associated with an increased risk for several cancer types and an altered phenotype and functionality of natural killer (NK) cells. This study aimed to investigate the association of overweight and obesity with NK cell functions and receptor expression profiles in humans. Therefore, peripheral blood mononuclear cells (PBMCs) were isolated from normal weight, overweight and obese healthy blood donors. In depth analysis of immune cell populations and 23 different surface markers, including NK cell receptors, NK-cell-related markers as well as functional intracellular markers on total NK cells and NK subgroups were performed by multicolor flow cytometry. The data revealed a decreased expression of the activating NK cell receptors KIR2DS4 and NKp46 as well as an increased expression of the inhibitory NK cell receptors NKG2A and Siglec-7 in overweight and obese compared to normal weight individuals. Additionally, the expression of the adhesion molecule CD62L and the maturation and differentiation marker CD27 was downregulated in NK cells of overweight and obese subjects. Furthermore, the cytotoxicity of NK cells against colorectal cancer cells was decreased in overweight and obese subjects. Investigations on underlying killing mechanisms demonstrated a reduced TRAIL expression on NK cells of obese subjects suggesting an impaired death receptor pathway in obesity. The present study gives new insights into an impaired functionality and phenotype of NK cells and NK cell subsets in overweight and obesity. These phenotypic alterations and dysfunction of NK cells might be an explanation for the increased cancer risk in obesity.